Laboratory Testing of Solar Combi System with Compact Long Term PCM Heat Storage. (June 2016) - Johansen, Jakob Berg; Englmair, Gerald; Dannemand, Mark; Kong, Weiqiang; Fan, Jianhua; Dragsted, Janne; Perers, Bengt; Furbo, Simon
Abstract: To enable the transition from fossil fuels as a primary heat source for domestic hot water preparation and space heating solar thermal energy has great potential. The heat from the sun has the disadvantage that it is not always available when there is a demand. To solve this mismatch a thermal seasonal storage can be used to store excess heat from the summer to the winter when the demand is higher than the supply. Installing a long term thermal storage in a one family house it needs to be compact and sensible heat storages are not suitable. A latent heat storage with a phase change material (PCM) can provide a more compact way of storing heat. Sodium acetate trihydrate (SAT) is a good candidate material as it has a relatively high heat of fusion and in addition it has the ability to supercool to room temperature without solidifying. In this paper results from the test of a solar combi system with a latent heat storage with SAT is presented. The SAT heat storage modules were heated to 80 °C by the solar collectors 53 times in the test period from June to November 2015 and this enabled the modules to supercool. Supercooling was achieved for 39 days for a SAT module after which 11 kWh of heat were discharged.